Variations in CD14 Gene Are Associated With Autoimmune Thyroid Diseases in the Chinese Population - Jia, Xi; Wang, Bing; Yao, Qiuming; Li, Qian; Zhang, Jinan (Frontiers in Endocrinology, 2019)
Autoimmune thyroid diseases (AITDs) are chronic organ-specific autoimmune diseases and mainly include Graves’ disease (GD) and Hashimoto’s thyroiditis (HT). CD14 is an important component of the immune system as a receptor for gram-negative lipopolysaccharide. The genetic polymorphisms of CD14 have been confirmed to be associated with a variety of autoimmune diseases. However, its relationship with AITDs is still unclear. The study was aimed to determine whether four single nucleotide polymorphisms (rs2915863, rs2569190, rs2569192, and rs2563298) of CD14 are associated with AITDs and its subgroups of GD and HT. The results showed significant association of rs2915863 and rs2569190 with GD. The frequencies of rs2915863 genotypes and T allele in patients with GD differed significantly from their controls (P=0.007 and P=0.021, respectively). For rs2569190, frequencies of genotypes and G allele in GD patients also showed positive P values (P = 0.038 and P = 0.027, respectively). The correlations between these two loci and GD are more pronounced in female GD patients and patients with a family history. In genetic model analysis, the allele model, recessive model and homozygous model of rs2915863 and rs2569190 embodied strong correlations with GD after the adjusting of age and gender (P=0.014, P=0.015, P=0.009 and P=0.014, P=0.001, P=0.006, respectively). However, these four sites are not related to HT. We firstly discovered the relationship between CD14 gene polymorphism and GD, and the results indicate that CD14 is an important risk locus for AITD and its SNPs may contribute to host's genetic predisposition to GD.